Sonic hedgehog is a chemoattractant for midbrain dopaminergic axons. - Rachel Hammond; Sandra Blaess; Asa Abeliovich (PLoS ONE, 2009)
Midbrain dopaminergic axons project from the substantia nigra (SN) and the ventral tegmental area (VTA) to rostral target tissues, including the striatum, pallidum, and hypothalamus. The axons from the medially located VTA project primarily to more medial target tissues in the forebrain, whereas the more lateral SN axons project to lateral targets including the dorsolateral striatum. This structural diversity underlies the distinct functions of these pathways. Although a number of guidance cues have been implicated in the formation of the distinct axonal projections of the SN and VTA, the molecular basis of their diversity remains unclear. Here we investigate the molecular basis of structural diversity in mDN axonal projections. We find that Sonic Hedgehog (Shh) is expressed at a choice point in the course of the rostral dopaminergic projections. Furthermore, in midbrain explants, dopaminergic projections are attracted to a Shh source. Finally, in mice in which Shh signaling is inactivated during late neuronal development, the most medial dopaminergic projections are deficient. In addition to the role of Shh in the induction of mDN precursors, Shh plays an important role in dopaminergic axon pathfinding to rostral target tissues. Furthermore, Shh signaling is involved in determining the structural diversity of these dopaminergic projections.